Analysis of the need for an update of the guidance documents. (6th May 2016) - ,
Abstract: The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel) adopted a series of guidance documents which complement the Regulations governing the authorisation of feed additives. These are intended to help applicants in their preparation of technical dossiers. Although most guidance documents prepared by the Panel have been updated at some point, experience has shown that some elements are in need of technical update. Consequently, the EFSA has asked the FEEDAP Panel to identify from the current guidance documents those that need to be updated. The FEEDAP Panel addressed this by considering the experience gained since the last major revision of the individual guidance documents. Each of the Standing Working Groups of the FEEDAP Panel were asked to identify issues which have arisen during additive assessments and which suggested the need for elements of the guidance to be reconsidered. In addition, consideration was given to the relevant overarching guidance documents produced by the EFSA Scientific Committee and to developments in assessment tools provided by EFSA and other international organisations. The analysis of the information collected indicated a number of broad areas in the existing guidance which need possible revision. In particular, since the existing guidance on environmental risk assessment is no longer aligned to other EFSA outputs, the Panel proposes that revision of this guidance should be given the highest priority. The Panel then proposes the revision of the three guidance documents concerned with safety (target animals, consumer and user) followed by the guidance on efficacy. In parallel, the data necessary to establish the characterisation of the additive should be reviewed and modified as necessary. The FEEDAP Panel considers it fundamental to involve industry, consumer associations and experts from Member States risk assessment bodies in the early stages of the guidance revision.